Insights into Going Concern Matter Disclosure in the Audit Report - Jannah, Miftahul; Ariani, Nita Erika; Nuraini A, Nuraini A; Lautania, Maya Febrianty (Universitas Syiah Kuala, 2025)
Objective This study examines the importance of business strategy in the acceptance of going concern matter disclosures in the audit report and whether corporate governance influences it. The main corporate governance factors examined are managerial ownership, institutional ownership, independent board of commissioners, and board of directors.Design/Methodology The population in this research consists of property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The sample was selected using a simple random sampling method, totaling 48 companies and 192 observations. The analytical method used in this study is logistic regression with SPSS 26.Results The study found that business strategy through product differentiation affects the acceptance of going concern matter disclosures in the audit report, while business strategy through cost advantage does not influence it. The board of directors, as part of corporate governance, influences the acceptance of going concern matter disclosures in the audit report, whereas managerial ownership, institutional ownership, and independent board of commissioners do not affect it.Research limitations/implications This research is limited to real estate companies, which limits the generalization of results to companies in other industries. Additionally, it does not consider individual auditors in auditor rotation but uses firm rotation, where the firm, according to regulations, does not have a time limit for providing audit services.Novelty/Originality This study introduces the utilization of business strategy in determining going concern matter disclosures in the audit report. Previous studies have predominantly focused on corporate governance in determining going concern matter disclosures in the audit report.